PENGARUH KONSENTRASI STARTER Acetobacter xylinum TERHADAP MUTU NATA DE CUCUMBER - Asnurita, I Ketut Budaraga, Yenti Mayang Sari (Jurnal Pertanian UMSB: Penelitian dan Kajian Ilmiah Bidang Pertanian, 2017)
The research titled Influence of Starter Acetobacter xylinum Concentration onQuality of Nata de Cucumber has been conducted at Center Instrumentation Laboratoryof Faculty of Agricultural Technology Andalas University Padang from September toNovember 2016. This study aims to determine the effect of starter concentration on natade cucumber quality and to know the concentration of starter optimal to produce aquality nata de cucumber. The experimental design used RAL with 5 treatments and 3replications. The observed data were analyzed by F test and then continued withDuncan's Multiple Range Test (DNMRT) test at 5% real level. The starter concentrationused 2.5%, 5%, 7.5%, 10%, and 12.5%. The results showed that starter concentrationhad an effect on rendement, coarse fiber content, and physical properties (elasticity,color / degree of white) at nata de cucumber. The optimal starter concentration in theproduction of nata de cucumber was obtained at treatment E with organolepticacceptance level and microbial content fulfill SNI, with quality characteristic is yield of90.15%, crude fiber content 1.92%, total microbial 2 × 102, elasticity 397, 36 N / cm2,white degree 53.16%.Keywords : Nata, cucumber, concentration, starter, quality